Rates of hospitalization associated with the use of aldosterone receptor antagonists in patients with pulmonary arterial hypertension. (August 2019) - Corkish, Morgan E.; Devine, Lauren T.; Clarke, Megan M.; Murray, Brian P.; Rose-Jones, Lisa J.
We show that spironolactone use was associated with an increased rate of all-cause hospitalizations, but no difference in hospitalizations for heart failure or pulmonary arterial hypertension, in patients with World Health Organization Group 1 pulmonary arterial hypertension. A possible reason for this finding is confounding from retrospective study design.